NORA'S DEVELOPMENTAL TRAJECTORY AS A LABYRINTH OF REALITY: A FEMINIST READING OF MATT HAIG'S THE MIDNIGHT LIBRARY - AHMED, SHOKHAN RASOOL (Journal of Duhok University, 2023)
With an emphasis on Nora's development as a character, this research presents a feminist interpretation of Matt Haig's book The Midnight Library (2020). The objective is to examine Nora's journey as she seeks a meaningful life amidst the intricate labyrinth by exploring diverse realities within the library, symbolizing the profound complexities experienced by women in a patriarchal society. This study employs feminist theory, which is the “umbrella” concept for many sub-feminism theories, where Nora's issues align with the strand of Feminist Psychodynamic Theory. The psychological implications of gender are investigated by feminist psychodynamic theory, which also examines how societal expectations, power relationships, and gender roles affect people's mental health. The feminist theory addresses three key issues about Nora's character. It uses Nora's experience with depression and suicidal thoughts as a lens through which to study how social conventions and gender expectations impact women's mental health. Furthermore, it examines how Nora's exploration of diverse life scenarios within the library sheds light on how patriarchal systems and other restrictive institutions curtail women's opportunities and choices. Ultimately, it delves into the significance of Nora's decision to reclaim agency over her life, symbolizing a feminist perspective on autonomy and empowerment. This study elucidates how gendered systems and societal expectations influence women's freedom of choice, mental well-being, and independence. It also delivers a feminist criticism of patriarchal oppression and depicts women as empowered as they negotiate the intricacies of reality through an analysis of Nora's journey utilizing feminist theory. The character of Nora from "The Midnight Library" is used in this study to demonstrate how gendered social norms affect women's autonomy, mental health, and opportunities for meaningful lives, and it also highlights the difficulties women face within patriarchal systems and emphasizes the necessity for empowerment and agency in the pursuit of meaningful lives.